PENGEMBANGAN E-MODUL PADA MATERI BILANGAN BULAT SMP KELAS VII - RIZA INDRIANY (Departemen Matematika, 2021)
The purpose of this study was to develop a learning tool in the form of a valid and practical E-Module on integer material for grade VII junior high school students. This research is a development research by modifying the Plomp development model which consists of three stages, namely preliminary research (Preliminary Research), making a prototype (Prototyping Stage), and the assessment phase (Assessment Phase).The preliminary research consists of needs analysis, curriculum analysis, concept analysis and student analysis. Making prototypes consisted of prototype 1, prototype 2, and prototype 3. In prototype 1, a self-evaluation was carried out, prototype 2 was conducted by an expert review by mathematics education experts to see the validity of the E-Module developed. While prototype 3 was carried out one to one evaluation by trying out the validated E-Module to three students with different learning abilities. The practicality of the E-Module is seen through the results of a practicality questionnaire on students' responses after one to one evaluation. Based on the results of the validity data analysis, it shows that the E-Module from the aspects of Self Instructional, Learning Materials, Stand Alone, User friendly, Display, Electronic Media, Multimedia Utilization, Software Use, E-Module Design, and Adaptive have a validity level of 84% with very categories. valid. The E-Module also fulfills practical criteria from the results of questionnaires and interviews. Based on these results, it can be concluded that the E-Module on integer material for grade VII junior high school students can be declared valid and practical.Keywords: Mathematics E-Module, Integer, Class VII Junior High School